2016
DOI: 10.1155/2016/7682387
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Exposure and Survival of Patients with Esophagus Cancer: A Systematic Review and Meta-Analysis

Abstract: Smoking is a well-known major risk factor in development of esophageal cancer, but few studies have reported the association between smoking status and prognosis of these patients. We conduct the present study to summarize current evidence. A computerized search of the PubMed and EMBASE was performed up to April 30, 2015. Eight studies, containing 4,286 patients, were analyzed. In the grouping analysis, among esophageal squamous-cell carcinoma patients, current and former smokers, compared to those who have ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…We have found that a 0.1 increase in the probability of smoking 1 year prior to diagnosis, adjusted for age and cancer stage at diagnosis, had an estimated HR of 1.20 (95% CI 1.18-1.22) in esophageal cancer survival. This association is consistent with findings from previous meta analyses such as HR 1.41 (95% CI 1.22,1.64) [21] for smoking status at time of diagnosis in mainly ESCC patients and HR 1.19 (95% CI 1.04,1.36) for ever smoking [4] in ESCC (although no evidence of association in EAC). Some more recently published studies found similar statistically significant HRs including HR = 1.28 [22] and HR = 1.34 [23] both from China, and HR = 1.22 from a study across two sites in US and Canada [24].…”
Section: Discussionsupporting
confidence: 92%
“…We have found that a 0.1 increase in the probability of smoking 1 year prior to diagnosis, adjusted for age and cancer stage at diagnosis, had an estimated HR of 1.20 (95% CI 1.18-1.22) in esophageal cancer survival. This association is consistent with findings from previous meta analyses such as HR 1.41 (95% CI 1.22,1.64) [21] for smoking status at time of diagnosis in mainly ESCC patients and HR 1.19 (95% CI 1.04,1.36) for ever smoking [4] in ESCC (although no evidence of association in EAC). Some more recently published studies found similar statistically significant HRs including HR = 1.28 [22] and HR = 1.34 [23] both from China, and HR = 1.22 from a study across two sites in US and Canada [24].…”
Section: Discussionsupporting
confidence: 92%
“…This implies that the unhealthy lifestyle (cigarette smoking, drinking alcohol, and betel quid chewing) of esophageal cancer patients can have a big impact on their remaining life. As stated by Ferronha l et al and Kuang JJ et al, many cancer survivors continue smoking and /or drinking even after diagnosis, which may result in a high cumulative exposures and poor survival [24][25][26] . As many as 27% of esophageal cancer patients have a chances of developing metachronous second primary cancer stated by Chen MF et al 13 in a study of a Taiwan nationwide esophageal cancer database from 1998-2007.…”
Section: Indicators Of Societal Burdens: Expected Years Of Life Loss mentioning
confidence: 98%
“…Son yıllarda yapılan bir meta analizde sigara içimi arttıkça (20 paket yıl ve üzeri) özellikle kemoradyoterapi alan grupta üç-beş yıllık yaşam süreleri anlamlı kısa bulunmuştur. Özefagus kanseri olan ve sigara içen grupta hiç sigara içme-yenlerle karşılaştırıldığında %41 oranında daha fazla ölüm görülmüş halihazırda sigara içen grubun yaşam süresi daha kısa bulunmuştur (13) .…”
Section: öZefagus Kanseriunclassified